Peningkatan Hasil Belajar Peserta Didik Kelas VII 3 SMP Negeri 10 Palembang Pada Materi Berbicara Dan Mempresentasikan Teks Tanggapan Dengan Menggunakan Model Problem Based Learning (PBL) - Zahara, Audi; Lestari, Hikmah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The aim of the PTK research is to determine the application of the Problem Based Learning (PBL) model in improving the learning outcomes of class VII 3 students at SMP Negeri 10 Palembang on speaking material and presenting response texts. This research was motivated by the low learning outcomes of class VII 3 students at SMP Negeri 10 Palembang due to the lack of interest and motivation to learn when students and educators still used conventional methods. The research method used is Classroom Action Research (PTK) with two cycles. The stages of this research are planning, implementation, observation and reflection. Data collection techniques in this research are observation and tests. Data collection instruments include test question sheets, teaching modules and LKPD. The data analysis technique is in the form of analysis of student learning outcomes using scoring guidelines. Based on the research that has been carried out, it can be concluded that there has been an increase in the learning outcomes of class VII 3 students at SMP Negeri 10 Palembang in the material of speaking and presenting response texts from Cycle I to Cycle II with the percentage of Cycle I learning outcomes being only 16 students (44.4% ) who achieved learning completeness, while 20 students (55.6%) had not yet achieved learning completeness. In Cycle II there was an increase where 33 students (91.6%) achieved learning completeness, while 3 students (8.4%) had not yet achieved learning completeness.